The Association of FTO SNP rs9939609 with Weight Gain at University - Susanne F. Meisel; Rebecca J. Beeken; Cornelia H.M. van Jaarsveld; Jane Wardle (Obesity Facts, 2015)
Aim: We tested the hypothesis that the obesity-associated FTO SNP rs9939609 would be associated with clinically significant weight gain (≥5% of initial body weight) in the first year of university; a time identified as high risk for weight gain. Methods: We collected anthropometric data from university students (n = 1,411, mean age: 22.4 ± 2.5 years, 49.1% male) at the beginning and end of the academic year. DNA was analysed for FTO rs9939609. Associations of FTO genotype with BMI at baseline were analysed using ANCOVA, and with risk of 5% weight gain over follow-up with logistic regression; both analyses adjusting for age and sex. The alpha level was reduced to 0.0125 to account for multiple testing. Results: Using an additive model, FTO status was not associated with higher BMI at baseline (22.2 vs. 21.9 kg/m2, p = 0.059). Dropout was high but unrelated to genotype. Among the 310 (21.9%) completing follow-up, those with AT genotypes had twice the odds of ≥5% weight gain compared with TTs (OR = 2.05, 95% CI = 1.05-4.01, p = 0.036), but this was no longer significant after Bonferroni correction. There was a trend for AA carriers for ≥5% weight gain compared with TT carriers (p = 0.089), but sample size was small. Conclusion: This study provides nominal evidence for the genetic susceptibility hypothesis, but findings need to be replicated.